The Vietnam reforms, change in wage inequality and the role of the minimum wage1. Issue 2 (22nd January 2014) - Sakellariou, Chris; Fang, Zheng
Abstract The Vietnam 'renovation' reforms were implemented during the 1990s, but their full effect was only felt several years later. We present evidence on the developments in real wage growth and inequality in Vietnam from 1998 to 2008. Using a variety of approaches (traditional measures of inequality, comparison of density functions, decomposition of the change in real wage by sector as well as a detailed decomposition of the change in the Gini), we present a consistent picture: contrary to what one might have expected given the nature of the reforms, inequality declined sharply in the private sector (but not in the state sector). This study links these developments to the policy of aggressively increasing the minimum wage over the past several years, differences in implementation by sector as well as variation in the over‐time changes in minimum wage.